Structure of the HNK-1 carbohydrate epitope on bovine peripheral myelin glycoprotein P0 - Vliegenthart, J.F.G.; Voshol, H.; Zuylen, C.W.E.M. van; Orberger, G.; Schachner, M. (Highwire, 1996)
The HNK-1 carbohydrate epitope, expressed by many neural recognition molecules, is involved in cell interactions that control cell type-specific neurite outgrowth and regeneration. It is also the target for autoimmune IgM antibodies in demyelinating neuropathies of the peripheral nervous system in humans. Despite its acknowledged importance in cell interactions, the HNK-1 carbohydrate structure, when expressed on glycoproteins, is still unknown. Here, we describe the structure of one of the predominant HNK-1-bearing glycans of bovine P0. The epitope consists of the sulfated trisaccharide SO4-3GlcA1-3Gal1-4GlcNAc, attached to the 1-6 arm of a diantennary core with a bisecting N-acetylglucosamine. It is the first example of a terminal 3-sulfated glucuronic acid on an asparagine-linked carbohydrate. Because the similarity between the glycoprotein-derived structure and the glycosphingolipids carrying HNK-1 is restricted to the terminal sulfated trisaccharide, we conclude that this element is sufficient for HNK-1 immunoreactivity. Knowledge of the HNK-1 structure on proteins is an important prerequisite for the elucidation of its functional role in development and disease.
Keywords: Scheikunde